A Review of Energy Storage Systems (ESS) for Integrating Renewable Energies in Microgrids - Patwary, Abdul Karim; Sayem, Md Abu; Hossain, Md Alom; Halim, Md. Abdul (Peneliti Teknologi Teknik Indonesia, 2024)
This review's primary goal is to include an energy storage system for incorporating renewable energy into microgrids. Both the integration of renewable energy sources with microgrids and the use of inappropriate storage systems are detrimental to renewable energy. Energy Storage Systems (ESS) are essential for facilitating the efficient integration of renewable energy sources in microgrids and resolving the intermittency and variable issues posed by these sources. Modern energy storage techniques and their use in microgrids are thoroughly reviewed in this paper. Renewable energy sources like solar panels, wind turbines, and occasionally biomass or small-scale hydropower are being integrated into microgrid designs more and more. Resilient and sustainable energy supplies are enhanced by this integration. Continuous advancements are made in the dynamic field of microgrid integration with renewable energy sources. However, there are still a lot of difficulties with integration, such as intermittent and variable performance, financial and technological obstacles, policy and regulatory problems, and grid connection difficulties. The review investigates how ESS can enhance grid stability, enhance energy management, and maximize the use of renewable energy sources. Various challenges of Renewable Energy Storage System have also been reviewed in this paper. Additionally, it looks at the opportunities and difficulties of adopting ESS in microgrids, including the requirement for effective deployment and control strategies. To show how effectively ESS enables the integration of renewable energies in microgrids, case studies and practical applications are discussed. The analysis concludes with suggestions for future research initiatives, highlighting the significance of developing ESS technologies to create robust and sustainable energy systems. This paper could end with suggestions for future research directions in the field of energy storage systems for microgrids, as well as recommendations for practitioners, policymakers, and researchers.